Analisis Spasial Angka Kematian Neonatal di Pulau Jawa Tahun 2020 - Prawira Yuda Husada; Aisyah Fitri Yuniasih (Seminar Nasional Official Statistics, 2022)
The high infant mortality in area can be described by the infant mortality rate. The infant mortality rate is very important because it’s able to describe the level of health and a reflection the level of social and economic development in a region. The purpose of this study was to obtain an overview of variables that affect the neonatal mortality rate in districts/cities in Java Island in 2020 using spatial regression method. The results showed that the variables of low birth weight and obstetric complications coverage had a positive effect, while the coverage of K4 visits had a negative effect on the neonatal mortality rate in the districts/cities of Java Island. Based on these results, the community and government are expected to pay more attention to condition of newborns, improve health services by building more equitable facilities, and improve the quality of health workers to reduce neonatal mortality in Java.